FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013-2015 - Novy Rachmawati, 14.05.62.0033; Badjuri, Achmad (Students Journal of Accounting and Banking, 2018)
This study aims to examine the factors that affect the value of companies in manufacturing companies. Through the implementation of the financial management functions carefully and appropriately in any financial decisions taken will affect other financial decisions that will impact the value of the company. The population of this study is a company listed on the Indonesia Stock Exchange (IDX) period 2013-2015. Sampling method using purposive sampling, the technique of determining the sample with certain considerations. The sample included in this research is 29 companies. Methods of data analysis in this study using multiple linear analysis using SPSS program. The result of the research shows that the variable of institutional ownership has negative effect not significant to firm value, dividend policy variable has a significant negative effect to firm value, investment decision variable and profitability variable have positive significant effect to firm value, funding decision variable and firm size variable have positive significant against company value,Keywords: Company value, institutional ownership, investment decision, funding decision, dividend policy, profitability, firm size